Task Analysis of the AF10 - A usability study to identify user experience issues - Polheimer, Frida; Ropel, Andreas (My University, 2010)
This report describes usability studies conducted in connection with the installation and configuration of a product, where focus has been specifically on the Ethernet configuration. The purpose of this study is to identify the most complicated tasks of the product’s configuration tool, and propose improvements. Ethernet is a relatively new technology for the product, and requires new functionality in its configuration tool. Observations have been carried out both internally and among the customers to identify inadequacies in the configuration tool which may have negative consequences to the product’s performance. The observations were carried out with the customers as the study participants, and the observations were supplemented by questionnaires and interviews to ensure reliable data. The studies resulted in 14 improvement proposals to facilitate the tasks of the configuration tool. Four of these 14 improvements were chosen for implementation in the first implementation phase. These improvements were the ones that would imply the biggest usability gain and have been described in more detail along with visualization. The vision from the company is that their configuration should be an easy task which makes it possible for anyone to install and configure the product. In order to realize this vision, the results from this usability study are of great importance.
Keywords: Information Technology; Informationsteknik